Feasibility and benefits of computerized cognitive exercise to adults with chronic moderate-to-severe cognitive impairments following an acquired brain injury: A pilot study. (5th December 2016) - O'Neil-Pirozzi, Therese M.; Hsu, Henry
Abstract: Primary objective : The purpose of this pilot study was to explore feasibility and effects of participation in a computerized cognitive fitness exercise program by a group of adults with chronic moderate-to-severe cognitive impairments following an acquired brain injury (ABI). Research design : This study used a mixed methods design with a convenience sample of individuals forming two groups (+/– exercise). Methods and procedures : Following neurocognitive and satisfaction with life pre-testing of 14 participants, seven were enrolled in a 5-month, 5-days a week computerized cognitive exercise program. Post-testing of all participants and semi-structured interviews of exercise group participants were completed. Main outcomes and results : It was feasible for adults with chronic moderate-to-severe cognitive impairments post-ABI to participate in a computerized cognitive exercise program with ongoing external cues to initiate exercise sessions and/or to complete them as needed. Significant exercise group improvements were made on memory and verbal fluency post-tests and life satisfaction. The majority of exercise group participants reported some degree of positive impact on cognitive abilities and some on everyday functioning from program participation. Conclusions : Adults with chronic moderate-to-severe cognitive impairments following an ABI may benefit from participation in computerized cognitive exercise programs. Further study is warranted.